Epoxy Self-Healing Coating by Encapsulated Epoxy Ester Resin in Poly (Urea-Formaldehyde-Melamine) Microcapsules - Cotting, Fernando; Koebsch, André; Aoki, Idalina Vieira (Frontiers in Materials, 2019)
In this work, poly (urea-formaldehyde-melamine) (PUFM) microcapsules containing a commercial epoxy ester resin were synthetized by in-situ polymerization technique. The microcapsules size distribution was analyzed by laser diffraction and the obtained microcapsules were evaluated by the Fourier-transform infrared spectroscopy (FTIR), in order to prove the ester epoxy resin microencapsulation. The filled microcapsules were incorporated in an epoxy three layer coating system, varying the microcapsules concentration (10 % and 15 %) and the microcapsules incorporation on the different layers - first, second or both. The coatings electrochemical behaviors were evaluated by electrochemical impedance spectroscopy (EIS) technique and localized scanning vibrating electrode technique (SVET). Pull-off adhesion tests were performed in the coatings systems, in order to verify if the microcapsules presence did affect the adhesion and/or cohesion coating properties. The EIS results showed that microcapsules change the coating electrochemical response, but the samples visual aspect suggests that the microcapsules improve the barrier properties of the microcapsules systems. The coating system containing the microcapsules showed a significant self-healing effect when stressed by a mechanical defect and the higher concentration (15 wt. %) of microcapsules provided a better self-healing protection, with better anticorrosive performance. Additionally, the microcapsules did not disturb the adhesion/cohesion properties of the coating system.